Children's Oncology Group's 2013 blueprint for research: Bone tumors. Issue 6 (19th December 2012) - Gorlick, Richard; Janeway, Katherine; Lessnick, Stephen; Randall, R. Lor; Marina, Neyssa; ,
Abstract In the US, approximately 650 children are diagnosed with osteosarcoma and Ewing sarcoma (ES) each year. Five‐year survival ranges from 65% to 75% for localized disease and <30% for patients with metastases. Recent findings include interval‐compressed five drug chemotherapy improves survival with localized ES. In osteosarcoma a large international trial investigating the addition of ifosfamide/etoposide or interferon to standard therapy has completed accrual. For ES an ongoing trial explores the addition of cyclophosphamide/topotecan to interval‐compressed chemotherapy. Trials planned by the Children's Oncology Group will investigate new target(s) including IGF‐1R and mTOR in ES, and RANKL and GD2 in osteosarcoma. Pediatr Blood Cancer 2013; 60: 1009–1015. © 2012 Wiley Periodicals, Inc.